2016
DOI: 10.1177/1747493015609776
|View full text |Cite
|
Sign up to set email alerts
|

Quality adjusted life year gains associated with administration of recombinant tissue-type plasminogen activator for treatment of acute ischemic stroke: 1998–2011

Abstract: r-tPA for AIS has resulted in estimated gains in quality-adjusted life years due to reduction in disability and improvement in functioning since its introduction in 1998.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Since the USA Food and Drug Administration (FDA) approval in 1996, there has been a small, yet gradual increase in the utilisation of rtPA for treatment of AIS (Lubeck et al, 2016). Results from the NINDS (1995) Study Group demonstrated that rtPA improved functional outcome after ischaemic stroke when given within three hours of symptom onset.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the USA Food and Drug Administration (FDA) approval in 1996, there has been a small, yet gradual increase in the utilisation of rtPA for treatment of AIS (Lubeck et al, 2016). Results from the NINDS (1995) Study Group demonstrated that rtPA improved functional outcome after ischaemic stroke when given within three hours of symptom onset.…”
Section: Discussionmentioning
confidence: 99%
“…In 11 of the studies, follow-up was assessed with the modified Rankin Scale (mRS) ( Table I). The mRS is a seven-point scale that progresses from 0 (no symptoms) to 6 (death) with varying levels of disability (Lubeck et al, 2016).…”
Section: Outcome Measuresmentioning
confidence: 99%